Ecofisiologia de mudas de ipê-roxo (Tabebuia impetiginosa Mart. ex. DC. Standal.) submetidas a estresse hídrico - Tomczak, Valmor Elias (Universidade Federal Rural do Semi-Árido, 2012)
Tabebuia impetiginosa is a tree species, known as pau d'arco or ipe-roxo. It is found in Caatinga areas, and is of great importance to this biome, its wood is much appreciated, and because it contains in its bark substances that act against cancer. This species has been used in land restoration programs. Species of this biome, such as ipe-roxo, present several morphophysiological changes as a way to adapt to the dry seasons of the year. The study of these changes is of great importance, and it s necessary to understand these mechanisms so that we can manage and conserve these species. Therefore, this study aims to evaluate the ecophysiological behavior of Tabebuia impetiginosa in response to water stress and rehydration. For this purpose an experiment was conducted in a greenhouse at the Universidade Federal Rural do Semi-Arido. The fruits were collected from trees of the same University and sowed in soil from two locations, Mossoro, and Angicos, this one collected in an area in process of desertification. When the seedlings reached nine months in the dry season, the treatments were applied, consisted of a set of two factors. the first one were the two soil types (Mossoró and Angicos) and the second, two water regimes with three replications, with each repetition represented by three plants. The evaluations were performed every three days during the period of suspension of irrigation in seedlings with and without irrigation, and the return of irrigation determined by monitoring the onset of leaf fall in plants subjected to irrigation suspension. After this period the plants were rehydrated, and evaluations done until the photosynthesis rates of the seedlings that were subjected to irrigation suspension equalized to the ones that were not submitted. The variables investigated were photosynthesis (A), stomatal conductance (E), internal CO2 concentration (Ci), transpiration (E), water use efficiency (A/E), carboxylation efficiency (A/Ci) and leaf water potential (Ψw) at predawn and midday.The soil of Mossoro presented greater rates of A and E in some evaluations when exposed to good water conditions when compared to the Angicos soil. This response in this condition was not related to gs. When subjected to stress, the of ipe-roxo seedlings in Angicos soil reduced their leaf Ψw before the seedlings grown in Mossoro soil. When rehydrated, seedlings grown in Angicos soil recovered their leaf Ψw before the plants grown in Mossoro soil. Regardless of the soil, water stress affected A, E, gs, and Ci, with decrease of these variables and rapid recovery after rehydration. In contrast, there was an increase in A/E during water stress, and this occurred earlier in plants grown in Mossoro soil. With water stress there was a the reduction of leaf Ψw, this reduction being found earlier in Angicos soil and in predawn. The Tabebuia impetiginosa presents itself as an investor plant, with an ability to reduce its leaf Ψw in water shortage conditions
Ecophysiology of ipe-roxo (Tabebuia impetiginosa Mart. ex. Dc. Standl.) plantlets, subjected to drought stress in greenhouse
Keywords: photosynthesis; water potential; stomatal conductance; Transpiration; Caatinga; Fotossítese; Potencial hídrico; Condutância estomática; Transpiração; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA